Studies on the mechanisms by which clenbuterol, a beta-adrenoceptor agonist, enhances 5-HT-mediated behaviour and increases metabolism of 5-HT in the brain of the rat. - Nimgaonkar, V; Green, A; Cowen, P; Heal, D; Grahame-Smith, D; Deakin, J (1983)
The head twitch response in mice produced by injection of 5-hydroxytryptophan (100 mg/kg i.p.) and carbidopa (25 mg/kg i.p.) was enhanced by administration of clenbuterol (0.5 mg/kg i.p.), a beta-adrenoceptor agonist. Clenbuterol also enhanced the hyperactivity syndrome in rats produced by quipazine (25 mg/kg i.p.), a 5-hydroxytryptamine (5-HT) agonist. This enhancement was not prevented by depletion of 5-HT in brain with p-chlorophenylalanine or after pretreatment with prazosin. The behavioural responses of the rats to administration of the alpha 2-adrenoceptor agonist, clonidine, was unaltered by acute or longer-term administration of clenbuterol. Following chronic administration of clenbuterol (5 mg/kg daily for 14 days), a procedure resulting in down-regulation of central beta-adrenoceptors, a larger dose of clenbuterol was necessary to enhance the quipazine-induced hyperactivity, suggesting that the mechanism of enhancement involved central post-synaptic beta-adrenoceptors. Further evidence for this conclusion was that a lesion of central noradrenaline pathways produced by 6-hydroxydopamine did not abolish the clenbuterol-induced enhancement of the quipazine-mediated behaviour. The binding characteristics of 5-HT2-receptors were unchanged by acute or chronic administration of clenbuterol. Clenbuterol (5 mg/kg) increased the percentage of plasma free (non-albumin bound) tryptophan, plasma free fatty acid concentration and the concentration of tryptophan and 5-hydroxyindoleacetic acid (5-HIAA) in the brain. The increase in 5-HT turnover in brain was prevented by pretreatment with the beta 1-adrenoceptor antagonist atenolol, which enters the brain poorly. It is therefore suggested that the clenbuterol-induced increase in 5-HT metabolism results from the increase in the concentration of plasma free fatty acid which increases plasma free tryptophan and thus increases the concentration of tryptophan in brain and 5-HT synthesis in brain. The clenbuterol-induced enhancement of 5-HT-mediated behaviour is therefore not associated with its effect on 5-HT metabolism. The data are discussed in relation to that obtained after administration of antidepressant drugs.